Competitiveness and external imbalances within the euro area (European Central Bank (ECB), 2012)
The onset of the financial crisis in 2008 has highlighted the problems of diverging external imbalances within Economic and Monetary Union (EMU) and the role of persistent losses in competitiveness. This paper starts by investigating some of the competitiveness factors which contributed to external imbalances in euro area countries. The evidence suggests significant heterogeneity across countries in both price/cost and non-price competitiveness in the euro area and that there is no one factor, but rather a range of potential factors explaining diverging external imbalances. In particular, while non-price competitiveness effects contributed largely to the trade surplus in some countries, for some southern European countries the trade balance was also driven by price factors. The second part of the paper studies the implications of competitiveness adjustment by means of quantitative tools. Using four different multi-country macro models, improvements in both price/cost aspects (namely wage reduction, productivity improvements or fiscal devaluation) and non-price competitiveness factors (quality improvements) were shown – under certain conditions – to improve external imbalances. The analysis suggests differences in countries' composition of trade could lead to heterogeneity in the potential gains from improvements in competitiveness.
Keywords: F30; E60; E65; E44; 330; competitiveness; euro area; macro models; open economy; simulations; Trade; Internationaler Wettbewerb; Handelsbilanz; Außenwirtschaftliches Gleichgewicht; Eurozone